Concept and Essence of Social Supply Chain and Professional Self-Determination in education System - Elena Sergeevna, Sergushina; Oleg Vladimirovich, Kabanov; Julia Evgenievna, Starostina; Lyudmila Leonidovna, Dragileva; Valentina Nikolaevna, Everstova; Alexander Valentinovich, Nikulin; Olga Sergeevna, Panova; Timur Niyazbekovich, Bekaliev; Artem Viktorovich, Popkov (International Journal of Supply Chain Management, 2020)
Abstract The author of this article reveals the content of the concepts of «identity», «professional identity», «social supply chain and professional identity» in education system. This topic has been recently studied as a system of value and supply of higher education. We made a conclusion about the need for the formation of social supply chain and professional identity of high school students, taking into account the spiritual and moral orientations, professional orientation, professional self-awareness of education system. The proposed social supply chain system can be effectively applied in the education system for various conditions.